Empirical Analysis of the Impact of Capital Structure on Firm Value — Based on the Empirical Data of High-Tech Listed Enterprises (Journal of Global Humanities and Social Sciences, 2024)
This paper selects computer, communication and other electronic equipment manufacturing enterprises as the representative of high-tech enterprises, and takes the data of 76 listed high-tech enterprises in the industry from 2019 to 2020 as samples, and carries out empirical test and research analysis on the impact of capital structure on enterprise value. The research shows that for high-tech enterprises, there is a significant positive correlation between capital structure and enterprise value, enterprises can improve the capital structure appropriately within a reasonable range, and then promote the development of enterprises.